2006
DOI: 10.1182/blood-2006-08-040022
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive secretion of granulocyte-macrophage colony-stimulating factor (GM-CSF) mediates imatinib and nilotinib resistance in BCR/ABL+ progenitors via JAK-2/STAT-5 pathway activation

Abstract: IntroductionImatinib mesylate, or IM (Gleevec; Novartis Pharma, Basel, Switzerland), has demonstrated a remarkable efficacy in the treatment of BCR/ABL ϩ leukemias, with most patients in early chronic phase achieving complete cytogenetic remissions (CCRs). 1 Despite this, BCR/ABL ϩ disease remains detectable in essentially all patients with chronic-phase chronic myelogenous leukemia (CML), and CML always recurs after cessation of IM treatment. 2 This reflects disease persistence under IM therapy. Mechanisms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 45 publications
5
111
1
2
Order By: Relevance
“…Autocrine growth loops with IL3, GM-CSF or G-CSF have been described in BCR-ABL cell lines and in CD34 þ cells from CML. [22][23][24][25] Recently, Wang et al 26 reported increased secretion of GM-CSF, in imatiniband nilotinib-resistant cells from the LAMA cell line, and in CD34 þ progenitors from some imatinib-resistant patients with CML. This cytokine was able to protect cells naive to imatinib or nilotinib by activating JAK2/STAT5 and MEK/ERK.…”
Section: Discussionmentioning
confidence: 99%
“…Autocrine growth loops with IL3, GM-CSF or G-CSF have been described in BCR-ABL cell lines and in CD34 þ cells from CML. [22][23][24][25] Recently, Wang et al 26 reported increased secretion of GM-CSF, in imatiniband nilotinib-resistant cells from the LAMA cell line, and in CD34 þ progenitors from some imatinib-resistant patients with CML. This cytokine was able to protect cells naive to imatinib or nilotinib by activating JAK2/STAT5 and MEK/ERK.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that flow cytometric measurement of P-CRKL is highly concordant to Western blot analyses. 39 As shown in Figure 4a, untreated K562 parental cells exhibited high levels of P-CRKL, reflecting a high activity of BCR-ABL. Exposure to 500 nM imatinib or 25 nM nilotinib in the parental cell line resulted in a significant loss of CRKL phosphorylation (upper row).…”
Section: Abcg2 Prevents Imatinib-and Nilotinib-mediated Crkl Dephosphmentioning
confidence: 99%
“…Interestingly, another regulatory T-cell subset, namely invariant natural killer T (iNKT) cells, expresses CD116 through which GM-CSF regulates their effector differentiation. 6 Finally, the recent report that adaptive secretion of GM-CSF occurs in human progenitors 25 in BCR/ABL ϩ patients opens the possibility that GM-CSF may play a role in human peripheral Treg amplification upon transplantation with mobilized hematopoietic progenitors.…”
Section: Treg Expanded With Gm-csf Display Enhanced Suppressive Functionmentioning
confidence: 99%